Point Prevalence of Gastrointestinal Helminthiaisis in Buffaloes of Jammu, India - Mir, Muzaffar Rasool; Chishti, M.Z.; Rashid, Majidah; Rashid, Majidah; Dar, S.A.; Katoch, Rajash; Kuchay, J.A.; Dar, J.A. (Journal of Buffalo Science, 2013)
The present study was carried out to determine the prevalence of gastrointestinal helminthiasis in buffaloes of Jammu area of Jammu And Kashmir State for the period of one year. For this purpose, 173 faecal samples were collected from different areas (Bisnah, R S Pura, Sidrah, Jammu city and Akhnoor) of subtropical Jammu. Parasitological procedures used for the identification of helminthes were direct and indirect methods. The overall prevalence of helminthiasis was 38.72%. Helminthic infection was recorded throughout the year with seasonal variations.